2016
DOI: 10.3892/ol.2016.4825
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging findings of extraventricular anaplastic ependymoma: A report of 11 cases

Abstract: Abstract. Anaplastic ependymomas are rare malignant tumors of the central nervous system. Few studies are available regarding their neuroradiological characteristics. The present study aimed to retrospectively review a series of patients with extraventricular anaplastic ependymoma and to analyze the magnetic resonance imaging (MRI) characteristics to distinguish anaplastic ependymoma from other intracranial tumors. The clinical and pathological images of 11 patients who presented with histologically proven ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 29 publications
4
25
1
2
Order By: Relevance
“…Intratumoral hemorrhage indicated high-grade malignancy and extensive, abnormal vascularization (8). Previous studies demonstrated that cysts or necroses are features of anaplastic ependymomas, especially supratentorial neoplasms (2,7,(22)(23)(24). Cysts (particularly diameter larger than 1 cm) are frequently observed in supratentorial ependymomas, whereas infratentorial ependymomas tended to be associated with solid neoplasms (22,26).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Intratumoral hemorrhage indicated high-grade malignancy and extensive, abnormal vascularization (8). Previous studies demonstrated that cysts or necroses are features of anaplastic ependymomas, especially supratentorial neoplasms (2,7,(22)(23)(24). Cysts (particularly diameter larger than 1 cm) are frequently observed in supratentorial ependymomas, whereas infratentorial ependymomas tended to be associated with solid neoplasms (22,26).…”
Section: Discussionmentioning
confidence: 99%
“…Ependymomas, which are central nervous system (CNS) tumors, are commonly found in the fourth ventricle and arise from ependymal cells lining the ventricular system ( 1 ). Moreover, these tumors can occur anywhere within and even outside the CNS ( 2 4 ). Based on the World Health Organization (WHO) 2016 classification system, ependymomas are divided into three histological grades: grade I–III ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DWI may help in identifying areas of hypercellularity, characterised by signs of restricted diffusion. 23…”
Section: Microscopic Pathology and Neuroimagingmentioning
confidence: 99%
“…Ependymomas are rare neoplasms of the central nervous system (CNS), accounting for 3.14% of all CNS tumors or 3–9% of all intracranial glial neoplasms (Chen et al 2013 ). Among intracranial ependymomas, 60% are infratentorial, and 40% are supratentorial (Leng et al 2016 ). Supratentorial extraventricular ependymoma (SEE) occurs outside the ventricular system of the brain and accounts for approximately 50% of supratentorial ependymomas (Wang et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%